Facile synthesis and efficient electrochemiluminescence of a readily accessible pyridopyrimidine. Issue 71 (6th August 2018) - Zhang, Ruizhong; Tong, Feng; Yang, Liuqing; Adsetts, Jonathan Ralph; Yan, Tianhao; Wang, Ruiyao; Ding, Zhifeng; Wang, Hong-Bo
Abstract : Through a facile one-pot three-component reaction and a subsequent acetylation strategy, a novel greenish-blue fluorescent 4-imino-4 H -pyrido[1, 2- a ]pyrimidine-3-carbonitrile (IPPC) was synthesized. Abstract : Through a facile one-pot three-component reaction and a subsequent acetylation strategy, a novel greenish-blue fluorescent 4-imino-4 H -pyrido[1, 2- a ]pyrimidine-3-carbonitrile (IPPC) was synthesized. Electrochemiluminescence (ECL) of IPPC was firstly found to produce efficient emission at 500 nm with reducing coreactants. Its very similar ECL and PL spectra suggest that ECL production is mainly from the monomeric excited states.